The pandemic century a history of global contagion from the Spanish flu to Covid-19 - Honigsbaum, Mark (WH Allen, an imprint of Ebury Publishing, 2020)
The most timely and informative history book you will read this year, tracing a century of pandemics, with a new chapter on COVID-19. Ever since the 1918 Spanish influenza pandemic, scientists have dreamed of preventing catastrophic outbreaks of infectious disease. Yet, despite a century of medical progress, viral and bacterial disasters continue to take us by surprise, inciting panic and dominating news cycles. From the Spanish flu and the 1924 outbreak of pneumonic plague in Los Angeles, to the 1930 'parrot fever' pandemic and the more recent SARS, Ebola, Zika and - now - COVID-19 epidemics, the last 100 years have been marked by a succession of unanticipated pandemic alarms. In The Pandemic Century, Mark Honigsbaum chronicles 100 years of history in 10 outbreaks. Bringing us right up-to-date with a new chapter on COVID-19, this fast-paced, critically-acclaimed book combines science history, medical sociology and thrilling front-line reportage to deliver the story of our times. As we meet dedicated disease detectives, obstructive public health officials, and gifted scientists often blinded by their own expertise, we come face-to-face with the brilliance and medical hubris shaping both the frontier of science - and the future of humanity's survival.